Higher Order Thinking Skills of Children Aged 4-6 Years in Early Language Learning Based on Lesson Study - Samad, Farida; Samad, Rita; Sasmayunita, Sasmayunita (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to describe the higher order thinking skills of children aged 4-6 years in early language learning based on lesson study. The research method used descriptive qualitative. The subjects of this study were B group students of Telkom Preschool Ternate in Â 2020/2021 academic year. Data collection was carried out using direct observation, in-depth interviews and documentation that explored children’s abilities of critical and creative thinking aspects. Data were analyzed which followed to the three main steps; data reduction, data presentation and verification, and concluding. The study found that early language learning based-on lesson study activities can stimulate children’s abilities in critical aspect; 18 students (81.8%) answered questions and retold and 4 students (18.2%) are able to interpret stories. Meanwhile, in creative thinking aspects 10 students (45.5%) have criteria that often appear of completing assignments in the form of the work given by the teacher. The children identify the problem, giving various responses and comments; become active learner both collaboratively in completing sharing and jumping tasks on â€˜ professionâ€™